1975
DOI: 10.1007/bf02425839
|View full text |Cite
|
Sign up to set email alerts
|

Blindness in mentally retarded children

Abstract: A preliminary survey of the causes of blindness in mentally retarded children in Denmark showed that 50% of the children had optic atrophy, 12.5% had cataract while tapeto-retinal degenerations, other malformation and retrolental fibroplasia each represents 8-9% of the causes of blindness. The survey, was done through written notification and some patients with tapeto-retinal degenerations might have been wrongly diagnosed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

1975
1975
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 2 publications
1
11
0
Order By: Relevance
“…According to a Danish study the cause of visual impairment in as many as 38% of mentally retarded children is optic atrophy (Warburg 1975). In our study we found this diagnosis in only 25% of the mentally retarded children, while 40% of the mentally retarded children had the diagnosis cerebral visual impairment.…”
Section: Discussionsupporting
confidence: 45%
See 2 more Smart Citations
“…According to a Danish study the cause of visual impairment in as many as 38% of mentally retarded children is optic atrophy (Warburg 1975). In our study we found this diagnosis in only 25% of the mentally retarded children, while 40% of the mentally retarded children had the diagnosis cerebral visual impairment.…”
Section: Discussionsupporting
confidence: 45%
“…The possible reason for this seems to be the fact that these children to a very large extent had additional impairments, rendering it harder to investigate and assess a visual impairment. The knowledge of the high frequency of visual impairment in multi-handicapped children (Warburg 1975) has given rise to an awareness of the condition and, in Sweden, an extensive referral of these patients to ophthalmologists, partly due to screening programmes for children with certain disorders. Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present survey and Table 1 show that the prevalence of VI is very high in adults with ID. This is not surprising since many national epidemiological studies have shown that half of blind children have ID (Warburg et al 1979; Riise et al 1992; Blomé & Tornqvist 1997). The reported prevalences of VI are variable and probably represent variable segments of the population with ID: the more people with DS (van Allen et al 1999; Van Buggenhout et al 1999), the higher the prevalence.…”
Section: Discussionmentioning
confidence: 96%
“…Visual impairment (VI) is common in children with intellectual disability (ID; Woodruff 1977; Warburg et al 1979; Woods 1979; Ronis 1989; Häussler et al 1996; Kwok et al 1996), but the prevalence in adults has been reported less often. Deinstitutionalization has been the policy in most industrialized countries for the past two decades.…”
Section: Introductionmentioning
confidence: 99%